The Difficult Hair Loss Patient Guide to Successful Management of Alopecia and Related Conditions - Trüeb, Ralph M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
You could read every textbook available on hair growth and disorders, and still not be able to treat hair loss effectively. In every art, there are many techniques, but few principles. The only way to achieve success is to have a firm foundation of principles to build upon, and the right attitude about how to achieve your goals. This book offers a detailed guide that goes beyond the technical aspects of trichology and evidence based medicine, providing specialists and primary care physicians experienced in the basic management of hair loss with the additional know-how they need to master the ultimate challenge of difficult hair loss patients. First, the prerequisites for successful management of hair loss are reviewed – basically, making a diagnosis and understanding the patient and his or her problem. Then, guidelines on the management of difficult dermatologic conditions and of psychopathological disorders associated with hair loss are provided. Lastly, important aspects of follow-up are covered–specifically the problems of adverse effects, patient non-compliance, and their management–before concluding with exemplary case studies of successful treatment of alopecia and related conditions.
Introduction: Defining the Difficult Hair Loss Patient -- Prerequisites for Successful Management of Hair Loss -- Patient Expectation Management -- The Difficult Dermatologic Condition -- Psychopathological Disorders -- Tackling Side-Effects -- Patient Non Compliance -- Optimizing Therapy Beyond Evidence Based Medicine -- Epilogue: Faith Healing.
Keywords: Dermatology; Dermatology